Electrochemical studies - Lu, Y (2022)
This thesis focuses on the electrochemical studies for two distinct purposes: one is to invent and validate an electrochemical sensor for detecting phosphate in natural aqueous solutions. The other is to develop a more comprehensive understanding of electrocatalysis at ensemble and single entity multiwalled carbon nanotubes (MWCNTs). Chapter 1 introduces essential background knowledge about fundamental electrochemistry and the generic electrochemical techniques used in this thesis and Chapter 2 gives a detailed description about experimental methods and materials characterization.